Front Cover: Complex pBAE Nanoparticle Cell Trafficking: Tracking Both Position and Composition Using Super Resolution Microscopy (ChemMedChem 13/2022). (5th July 2022) - Riera, Roger; Tauler, Jana; Feiner‐Gracia, Natàlia; Borrós, Salvador; Fornaguera, Cristina; Albertazzi, Lorenzo
Abstract : The Front Cover shows the trafficking of polyplexes inside cells to deliver oligonucleotides. Many steps are needed from internalization, endosomal escape, and decomplexation for a successful delivery, but they are too small to be visualized using classical fluorescence microscopy. Alternatively, the localization and composition of these nanomaterials can be studied using quantitative super‐resolution microscopy as shown in the STORM image of polyplexes in this cover. Created with Biorender.com by Roger Riera. More information can be found in the Full Paper by Roger Riera, Cristina Fornaguera, Lorenzo Albertazzi et al .